Biosensors: frontiers in rapid detection of COVID-19 - Samson, Rachel; Navale, Govinda R.; Dharne, Mahesh S. (3 Biotech, 2020)
The rapid community-spread of novel human coronavirus 2019 (nCOVID19 or SARS-Cov2) and morbidity statistics has put forth an unprecedented urge for rapid diagnostics for quick and sensitive detection followed by contact tracing and containment strategies, especially when no vaccine or therapeutics are known. Currently, quantitative real-time polymerase chain reaction (qRT-PCR) is being used widely to detect COVID-19 from various types of biological specimens, which is time-consuming, labor-intensive and may not be rapidly deployable in remote or resource-limited settings. This might lead to hindrance in acquiring realistic data of infectivity and community spread of SARS-CoV-2 in the population. This review summarizes the existing status of current diagnostic methods, their possible limitations, and the advantages of biosensor-based diagnostics over the conventional ones for the detection of SARS-Cov-2. Novel biosensors used to detect RNA-viruses include CRISPR-Cas9 based paper strip, nucleic-acid based, aptamer-based, antigen-Au/Ag nanoparticles-based electrochemical biosensor, optical biosensor, and Surface Plasmon Resonance. These could be effective tools for rapid, authentic, portable, and more promising diagnosis in the current pandemic that has affected the world economies and humanity. Present challenges and future perspectives of developing robust biosensors devices for rapid, scalable, and sensitive detection and management of COVID-19 are presented in light of the test-test-test theme of the World Health Organization (WHO).
Keywords: Biosensors; COVID-19; Rapid detection; SARS-CoV-2

Bacteriophages: status quo and emerging trends toward one health approach - Samson, Rachel; Dharne, Mahesh; Khairnar, Krishna (Science of The Total Environment, 2024)
The alarming rise in antimicrobial resistance (AMR) among the drug-resistant pathogens has been attributed to the ESKAPEE group (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumanii, Pseudomonas aeruginosa, Enterobacter sp., and Escherichia coli). Recently, these AMR microbes have become difficult to treat, as they have rendered the existing therapeutics ineffective. Thus, there is an urgent need for effective alternatives to lessen or eliminate the current infections and limit the spread of emerging diseases under the ``One Health'' framework. Bacteriophages (phages) are naturally occurring biological resources with extraordinary potential for biomedical, agriculture/food safety, environmental protection, and energy production. Specific unique properties of phages, such as their bactericidal activity, host specificity, potency, and biocompatibility, make them desirable candidates in therapeutics. The recent biotechnological advancement has broadened the repertoire of phage applications in nanoscience, material science, physical chemistry, and soft
Keywords: Antimicrobial resistance (AMR); Bacteriophages; One-health; Therapeutics commercialization